2011
DOI: 10.2807/ese.16.11.19820-en
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 2010/11 seasonal trivalent influenza vaccine in Spain: preliminary results of a case–control study

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 9 publications
4
31
2
1
Order By: Relevance
“…Also we have seen that having received both the pandemic and the current vaccine, protected against A(H1N1)pdm09 infection in 2010–2011, an effect also described in previous studies [14;26;27]. Within each studied season, we did not find any interference between the previous season’s vaccine and the current vaccine’s performance, findings also confirmed by the pooled analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Also we have seen that having received both the pandemic and the current vaccine, protected against A(H1N1)pdm09 infection in 2010–2011, an effect also described in previous studies [14;26;27]. Within each studied season, we did not find any interference between the previous season’s vaccine and the current vaccine’s performance, findings also confirmed by the pooled analysis.…”
Section: Discussionsupporting
confidence: 89%
“…A study by Kissling et al reported adjusted VE for eight EU states to be 52% overall and 41% for the 15 to 59 year age group [15]. Similar estimates were also reported by Steens et al for the Netherlands (46%) and by Savulescu et al for Spain (50%), both of which used a test-negative control comparison group [13], [14]. Contrary to our findings of no VE for the A/H1 subtype, Kissling et al reported a VE of 27% for A/H1 among 15 to 59 year olds, however, this did not reach statistical significance [15].…”
Section: Discussionsupporting
confidence: 62%
“…With the growing evidence on the questionable efficacy of influenza vaccines (86-89) and despite the lack of reliable sero-epidemiological studies, the pattern of laboratory-confirmed AH1N1 2009 mortality indicated that Western hemisphere countries achieved a higher degree of acquired active, infectious immunity than other world regions (Table 4, Figure 3). Also, the expected epidemiological effect of vaccine immunity was not achieved.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by the fact that people older than 55 years had lower morbidity in all parts of the world (7-67), indicating that they had been actively immunized with the infectious virus AH1N1 2009 during their life. No less important is the fact that infectious immunity provides a high degree of crossed immunity to other influenza viruses (90), while vaccine immunity lasts no longer than a year, is highly type-specific, and the possibility of crossed immunity is minimal (88,89,91). We believe that these findings clearly demonstrate that, from an epidemiological point of view, the vaccination for influenza during its outbreak should be reserved for health-risk groups.…”
Section: Resultsmentioning
confidence: 99%